Application of the HEC-RAS and HEC-HMS Models for Flood Risk Analysis in the Gumara River, Upper Blue Nile Basin, Ethiopia - Mulie Admas; Tade Mule Asrade; Walelgn Dilnesa Cherie (Advances in Meteorology)
In terms of socioeconomic damage, floods are one of the most destructive natural disasters. However, by conducting flood modeling prior to an event, their impacts can be mitigated and better managed. This study aims to assess flood risk areas in the Gumara River using HEC-RAS and HEC-HMS. Data on rainfall, stream flow, and spatial information were collected, including digital elevation models (DEMs), land use, and soil maps. Flood levels before and after dyke construction were examined using the HEC-RAS model. The impact of flood before construction of dyke for each return periods 2, 5, 10, 25, 50, and 100 years were 6232.64, 6262.51, 6375.04, 6495.62, 6639.55, and 6804.26 ha, respectively, and after dyke construction also 5912.18, 5966.47, 6027.13, 6108.04, and 6483.49 ha at the same return periods. The construction of dyke reduced impact of flooding for each return periods were 5.14%, 4.73%, 5.46%, 5.97%, 7.73%, and 4.71%, respectively. However, the dyke did not fully eliminate flood risks. Particularly during the summer months of July and August, the research area is still quite vulnerable. Based on these findings, the study recommends prioritizing the construction of a storage dam upstream of the Gumara Bridge, as it would offer more effective flood routing and protection for downstream settlements. River channelization and the addition of a silt excluder may provide supplementary benefits, particularly in maintaining flow capacity and reducing sediment buildup. Additional dykes and barriers along key tributaries could further mitigate localized flooding. However, these should be considered secondary measures following comprehensive upstream flood control through dam storage.